Conserving coastal colonies a center for research, restoration, and awareness of coral reefs : a study on the design of a coral nursery and its potential as a tool against climate change - Rafael, Roberto Felix H. (College of Architecture, University of the Philippines Diliman, 2022)
Coral reefs are a cornerstone of the underwater ecosystem by providing shelter to marine wildlife. However, due to rising ocean temperatures and acidity, these reefs have undergone rapid decline. This is exacerbated further by climate change's increasingly powerful typhoons that damage coral reefs. Camiguin is among this statistic, whose mass coral bleaching due to frequent typhoons have greatly affected its economy. Those living in poverty are extremely affected since fishing constitutes their sustenance and livelihood. Present studies have been made to counteract coral bleaching, notably the discovery of microfragmentation which accelerates the maturity of corals by up to 500%. Projects known as coral nurseries combat the onset of climate change by strengthening marine ecosystems through this technique. Land-based nurseries have also been developed to optimize the microfragmentation process through more control over the coral's incubation. An opportunity presents itself in Camiguin, whose constituents serve as stakeholders in the restoration of corals due to their influence over the island's fishing and booming tourist industry. This is mutually beneficial, as the biodiversity in the island could aid researchers in the coral conservation field. By developing a land-based coral nursery and research institution, one can improve the tourism of the province. This project will also involve the participation of the local community, taking a holistic, long-term approach by instilling social responsibility among Camiguin's residents. This will not only benefit the island but may also serve as a blueprint for the future projects, opening a network of coral research and restoration projects around the country.